Effects of different cooking methods on the lipids and volatile components of farmed and wild European sea bass (Dicentrarchus labrax). (January 2018) - Nieva-Echevarría, Bárbara; Goicoechea, Encarnación; Manzanos, María J.; Guillén, María D.
Abstract: European sea bass is very popular in the Mediterranean area, although very little is known about the possible different behaviours of farmed and wild samples during cooking. This study addresses the effect of microwave cooking, salt-crusted and conventional oven baking on the lipids and volatile profile of farmed and wild sea bass. Proton Nuclear Magnetic Resonance did not detect that hydrolysis or oxidation of lipidic components had taken place. However, Solid Phase Microextraction-Gas Chromatography/Mass Spectrometry evidenced that polyunsaturated acyl group oxidation and Maillard-type reactions occurred to a very slight extent, yielding a wide variety of volatile odour-active compounds. Conventional baking enriched fish volatile profile to a higher extent than the other two techniques assayed. In fact, 15 Maillard reaction-derived compounds (pyrroles, alkylpyrazines, alkylthiophenes and 2-ethylpyridine) were only detected in oven-baked samples. Regardless of the cooking method applied, farmed sea bass showed a much richer aromatic profile than did wild samples, having 6-fold higher lipid content than the latter. Graphical abstract: Highlights: Effect of microwave cooking, salt-crusted and conventional baking was studied. No changes detectable by 1 H NMR in lipid composition were observed after cooking. SPME-GC/MS evidenced that cooking modified sea bass volatile profile, mainly farmed. Main difference among cooking methods lied on Maillard reaction volatiles formation. Salt-crust protected against lipid oxidation and Maillard-type reactions.